Clinical characteristics and outcomes of PTLD following intestinal transplantation. Issue 8 (5th July 2018) - Wozniak, Laura J.; Mauer, Tian L.; Venick, Robert S.; Said, Jonathan W.; Kao, Roy L.; Kempert, Pamela; Marcus, Elizabeth A.; Hwang, Vilayphone; Cheng, Elaine Y.; Busuttil, Ronald W.; McDiarmid, Sue V.; Farmer, Douglas G.
Abstract: Post‐transplant lymphoproliferative disease (PTLD) has the highest incidence following intestinal transplantation (ITx). Our center has seen a recent increase in PTLD. Our aim was to review a single‐center PTLD experience with a focus on clinical characteristics and outcomes. We completed a retrospective review of biopsy‐proven PTLD cases using a prospectively maintained database of 115 ITx recipients transplanted between 1991 and 2014. Nineteen (17%) ITx recipients developed 25 PTLD cases during a median follow‐up time of 6.4 (1.6‐14.6) years. The incidence of early PTLD was 6% (n = 7). There was a trend toward increased risk of PTLD in children compared with adults ( P = .11) and a significantly increased risk of PTLD in re‐ITx compared with primary ITx recipients ( P = .03). Most PTLD cases were diagnosed between 2010 and 2014 (n = 14). All early PTLD cases were EBV+ on in situ hybridization. Overall graft and patient survival are 68% and 74%, respectively. Second episodes of PTLD were diagnosed in 43% of surviving pediatric patients. Our program has a low incidence of early PTLD with overall excellent graft and patient survival following diagnosis. However, we have also seen a rising incidence of late PTLD. The cause of the increase is unknown as no major changes in immunosuppression protocols have occurred since 1999.